(untitled) (Eurasian Journal of Philology Science and Education, 2025)
The first Kazakh meta role by Alibek Baibol is an innovative work that enriches modern Kazakh literature. In this novel, Baibol uses meta-narrative elements such as the author’s comments, reflections on the process of creating a text, and active communication with the reader. This makes it possible to rethink traditional narrative forms and deepen the understanding of the social and cultural realities of modern Kazakhstan. The novel serves as an important stage in developing national literature, stimulating critical thinking and self-awareness of both authors and readers. The relationship between the novel’s events and real historical and cultural events is deep. The motif of "awakening" can be traced in the work. In the novel, the author alludes to the reflection of the social and cultural realities of modern Kazakhstan. In the literature of the Turkic peoples of the late early XX centuries, the theme of "awakening" was widely raised. It is known that during that period, poets who wished their nation not to be late for civilization sang national unity and spiritual integrity in their works. This article analyzes the influence of the meta roman not only on setting new standards of literary creativity but also on integrating Kazakh literature into the world literary process, creating a unique and original literary tradition of Kazakhstan. Keywords: Kazakh novel, metaroman, meta-prose, Alibek Baybol, novel “Mūtylğan”.